Redefining Loyalty Programs: Gamification in Marketing - Dini Mardani, Agnes; Evrina, Evrina; Hartati, Bella (Takaza Innovatix Labs Ltd., 2024)
This qualitative study explores the impact of gamification on customer loyalty within the Tokopedia platform, a leading e-commerce marketplace in Indonesia. Through in-depth interviews and observations of 20-30 participants, the research investigates their perceptions of the loyalty program, experiences with gamified elements, and the overall effects on their loyalty to the brand. Findings indicate that participants generally appreciate the gamification features, which enhance engagement and foster emotional connections. However, concerns regarding the complexity of the rewards system and the sustainability of interest over time emerged. The study underscores the importance of simplifying loyalty program structures and integrating culturally relevant gamification elements to resonate with Indonesian consumers. It also highlights the need for continuous innovation in gamified features to maintain customer engagement in a competitive digital environment. The research contributes valuable insights for Tokopedia and similar platforms, suggesting strategies to optimize gamification in loyalty programs to enhance customer retention and satisfaction. Future research should explore gamification across multiple platforms and demographics to further understand its impact and efficacy in the e-commerce landscape.